Mikromorfologi Gonad dan Tipe Reproduksi Ikan Lempuk (Gobiopterus sp.) sebagai Informasi untuk Upaya Domestikasi - Latifa, Yusria; Farikhah, Farikhah; Hertika, Asus Maizar Suryanto (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Lempuk fish is a native Indonesian fish that is endemic in the Ranu Grati tectonic lake, Pasuruan Regency, East Java. This research aims to provide information in efforts to domesticate lempuk fish, especially on reproductive aspects related to the microscopic characteristics of gonads and reproductive type of Lempuk fish (Gobiopterus sp). This research uses the primary sexual characteristics method with gonadal histology. The variables observed included the male to female sex ratio, the histological structure of male and female gonads, and the reproductive type of lempuk fish. All data was analyzed descriptively, qualitatively and quantitatively by comparing with related literature. The samples taken in this research were 39 Lempuk Fish (Gobiopterus sp). The samples were then preserved in 10% formalin. The number of samples for histological analysis was 20 individuals, while for morphometric and meristic analysis there were 8 individuals. The results of the research show that morphologically the lempuk fish has a transparent body shape and there is a central line on the body with black or brown pigment and has a total length of around 2-3 cm. Lempuk fish have a type of reproduction that develops asynchronously (asynchronous) because the development of oocytes in the ovaries of female fish shows a variety of developmental stages, namely the initial growth stage (nuclear and perinuclear chromatin), cortical alveolar, vitellogenesis, and the mature stage. The sex ratio is predominantly female with a ratio of 0.64: 0.36. The histological structure of male and female gonads has histological differences that reflect different reproductive functions, where the ovaries play a role in egg cell production, while the testes are responsible for sperm formation. An imbalance in the sex ratio indicates the importance of carrying out domestication steps in order to prevent extinction or continuous population decline.